2013
DOI: 10.1364/ol.38.003558
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond double-pulse fabrication of hierarchical nanostructures based on electron dynamics control for high surface-enhanced Raman scattering

Abstract: This Letter presents a simple, efficient approach for high surface-enhanced Raman scattering by one-step controllable fabrication of hierarchical structures (nanoparticles+subwavelength ripples) on silicon substrates in silver nitrate solutions using femtosecond double pulses based on nanoscale electron dynamics control. As the delays of the double pulses increase from 0 fs to 1 ps, the hierarchical structures can be controlled with (1) nanoparticles--the number of nanoparticles in the range of 40-100 nm reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Therefore, the laser energy absorption is completed during the non-thermal process in significant electron-lattice non-equilibrium states. [27][28][29][30] It is worth noting that this approach of athermal reparation of nanoscale defects via a femtosecond laser is only applicable to optical materials so that the laser can penetrate into the bulk and effectively have the nanoscale defect repaired. In addition, though high spatial selectivity and low efficiency seem to be two sides of the same coin in this study, our approach could be combined with other thermal and ionization processes 35 to further improve the efficiency of defect reparation.…”
Section: Repair Processmentioning
confidence: 99%
“…Therefore, the laser energy absorption is completed during the non-thermal process in significant electron-lattice non-equilibrium states. [27][28][29][30] It is worth noting that this approach of athermal reparation of nanoscale defects via a femtosecond laser is only applicable to optical materials so that the laser can penetrate into the bulk and effectively have the nanoscale defect repaired. In addition, though high spatial selectivity and low efficiency seem to be two sides of the same coin in this study, our approach could be combined with other thermal and ionization processes 35 to further improve the efficiency of defect reparation.…”
Section: Repair Processmentioning
confidence: 99%
“…The femtosecond (fs) laser, a promising tool for processing a broad range of materials, including metals [1][2][3][4], semiconductors [5][6][7][8][9], and insulators [10][11][12][13], has attracted significant attention due to its wide range of potential applications in many fields, such as colorization [3,6,7], solar cells [5], waveguides [10], surface-enhanced Raman scattering [14,15], microchannels [16,17], and optical data storage [18]. For all of these applications, the forma-tion of well-defined, uniform submicroscale, even nanoscale, structures is a prerequisite.…”
Section: Introductionmentioning
confidence: 99%
“…With pulse delays in picoseconds, a monotonic decrease of ablation areas was observed as the pulse delay increased [6][7][8]. Surprisingly, some abrupt changes have also been obtained in experiments using fs double pulses with pulse delays in femtoseconds [9][10][11]. For example, Deng et al found that a systematic dip of the second pulse optical breakdown threshold in silica is observed for pulse delays from 200 to 300 fs [10].…”
mentioning
confidence: 99%
“…Femtosecond double pulses consist of two subpulses with a uniform intensity distribution and pulse delays ranging from several femtoseconds to several hundred picoseconds [6][7][8][9][10][11][12][13]. Femtosecond double pulses may make it possible to adjust the laser-material interaction process, as compared with the conventional fs pulse.…”
mentioning
confidence: 99%